The use of turbidity as a separation indicator of patchouli oil from its aqueous mixture in community distillation practices. (16th December 2019) - Cahyani, Chandrawati; Nirwana, Wa Ode Cakra
A laboratory study was conducted to investigate the possibility of patchouli oil separation from its aqueous mixture based on physical phenomena. The main concept behind the study was the application of turbidity instead of gas chromatography to determine the separation quality of patchouli oil from its aqueous mixture. This study proved that there was a linear relationship between turbidity and oil content in its water emulsion during distillation processes. The results showed that temperature, the addition of chemical agents, and pH influenced separation quality. A temperature of 60°C was proved to be the optimum separation temperature. At this temperature, separation required less cooling water, saving energy and streamlining the process. A pH of 4 was proved to be the best value, while NaCl was proved to be the best additive at a concentration of 0.2% in patchouli oil-water mixture.